Microchip fabrication : a practical guide to semiconductor processing - Van Zant, Peter (New York : McGraw-Hill Professional, 2014)
"This fully updated introduction to semiconductor manufacturing--the industry that drives high tech--offers a low-math, straightforward approach to the entire process, from raw materials through shipping the finished, packaged device"--
Includes bibliographical references and index.
Keywords: Semiconductors; Integrated circuits -- EE, EL